2021
DOI: 10.1002/onco.13915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes, Treatment Toxicity, and Health Care Utilization in Older Adults with Aggressive Non-Hodgkin Lymphoma

Abstract: Background. Although balancing treatment efficacy with risks of complications is critical for older adults with aggressive non-Hodgkin lymphoma (NHL), few studies have described these patients' clinical outcomes, rates of toxicities, and health care utilization. Methods. We conducted a retrospective analysis of adults ≥65 years diagnosed with aggressive NHL and receiving systemic therapy at Massachusetts General Hospital from April 2000 to July 2020. We abstracted patient characteristics, clinical outcomes, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…This may result in discrepancies in use of the overall FENCE score as a risk parameter because patients with advanced-stage disease received high-intensity chemotherapy, which is considered a risk factor for developing FN. The factors with the highest specificity in prediction of FN were hypoalbuminemia and receipt of platinum chemotherapy, which is similar to the standard guidelines ( 4 , 14 ). Platinum-based chemotherapy is the most common form of chemotherapy ( 8 ).…”
Section: Discussionsupporting
confidence: 71%
“…This may result in discrepancies in use of the overall FENCE score as a risk parameter because patients with advanced-stage disease received high-intensity chemotherapy, which is considered a risk factor for developing FN. The factors with the highest specificity in prediction of FN were hypoalbuminemia and receipt of platinum chemotherapy, which is similar to the standard guidelines ( 4 , 14 ). Platinum-based chemotherapy is the most common form of chemotherapy ( 8 ).…”
Section: Discussionsupporting
confidence: 71%
“…26,27 Moreover, a simplified geriatric assessment using age, comorbidities, and assessments of patients' activities of daily living and instrumental activities of daily living can risk stratify those with diffuse large B-cell lymphoma and could represent a novel treatment risk stratification approach. 28 Hypoalbuminemia has been shown in previous work to correlate with risk of toxicity in older adults with aggressive lymphomas, 29 but the mechanism through which it affects clinical outcomes remains unclear and could relate to nutritional status, comorbidities, and/or disease biology. 14,30 Notably, age, comorbidities, and hypoalbuminemia are clinical factors that could be readily incorporated as triggers to select patients with the greatest need for supportive care interventions such as geriatric interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue, in particular, can be severe, debilitating, and persistent even in survivorship [91][92][93]. More than 50% of NHL patients experience substantial treatment toxicities and high care utilization at the end of life [94]. One study of 91 older NHL patients with aggressive disease demonstrated that in the last 30 days of life, 70% were hospitalized, one-third received systemic Current Treatment Options in Oncology therapies, nearly one-quarter underwent admission to an intensive care unit, and more than half died in a healthcare facility.…”
Section: Symptom Burden and Palliative Care Needsmentioning
confidence: 99%